Starting over through different learning areas - Belchior-Rocha, H. (2022)
This paper aims to present a pilot study, with an action research methodology, in a campus recently created by a public university where an UpSkill: Digital Skills & Jobs program has been developed. This vocational training program is funded by the Institute of Employment and Vocational Training and is aimed at unemployed people who have at least secondary education and English language skills and who wish to obtain qualifications in the area of digital technologies. It integrates six months of intensive training in areas such as programming in several languages, cloud platform management, or low-code platform programming. However, this is a very diverse public, they can be individuals with master's, doctorate, or no higher education and even people who emigrated and now return to their country and have difficulties integrating into the labor market. Thus, two modules of transversal skills were developed, one for preparing the entry into the labor market and another for training interpersonal competencies when they are already in the organization that employed them. The two-course modules were based on an in-depth analysis and deconstruction of the concept of decent work (ILO 2019), with the purpose of developing the main axes that should be present in the active job search. The first-course module general orientation is to promote self-knowledge and skills assessment, the resources and abilities that each person possesses and that can be mobilized in the search for a job. This can enable students to make informed choices that enhance their knowledge and abilities, reconciling these guidelines with the opportunities. The second-course module invests in the development of interpersonal skills that enable students to enhance their individual abilities such as social skills (social interaction and cooperation, managing conflicts, teamwork, and communication skills). We know that any organization wants to have a team of employees that can work in full harmony, promoting a pleasant and healthy corporate space. However, the reality of teamwork and conflict management does not always correspond to such an expectation. In this context, applying conflict management strategies in the workplace becomes essential. From this experience, students evaluate their progress and we can share positive results of the evaluation of the seven groups (25 students each) formed so far and also their inclusion in the labor market that allowed them the possibility of starting over.